Exploring chemical analysis - Harris, Daniel C., 1948- (New York (N.Y.) : Freeman, 2009)
'Exploring Chemical Analysis' provides an ideal one-term introduction to analytical chemistry for students whose primary interests generally lie outside of chemistry. Combining coverage of all major analytical topics with effective problem-solving methods, it teaches students how to understand analytical results and how to use quantitative manipulations, preparing them for the problems they will encounter in fields from biology to chemistry to geology. The new edition includes new applications throughout, more emphasis on 'green chemistry,' and more integration of Excel.
Includes bibliographical references and index.
Keywords: Chemistry, Analytic